Multi‐site study exploring the experiences of security staff responding to mental health, drug health and behavioural challenges in the emergency department. (30th April 2020) - Wand, Timothy; Bell, Nerida; Stack, Amanda; Collett, Gemma; Cutten, Alexa; Murphy, Margaret; White, Kathryn
Abstract: Objective: This multi‐site study aimed to give voice to the views and experiences of security staff in assisting with the response to the growing number of people with mental health, drug health and behavioural problems attending EDs. Methods: Explorative qualitative research design, using semi‐structured interviews were conducted with security staff ( n = 26) working in three different emergency settings across New South Wales, Australia. The data were analysed thematically. Results: Participants recognised that long waiting times in the ED 'guarding' patients frequently accounted for escalating behaviour and increased the likelihood of restrictive interventions. Security staff expressed concerns about safety and were uncomfortable with a sense of uncertainty regarding their legal position. They voiced frustration over limited communication and lack of information provided by clinical staff on patient background, and the coordination of incidents and ongoing patient care. There was a perception that security staff are not treated with respect and their input was not valued. Conclusion: Expecting non‐clinicians to undertake a clinical role (often under stressful circumstances involving close patient contact) places security staff and patients in a precarious position. Greater clarity regarding the role of security staff and information that allows them to adequately and safely undertake their work is required. If security staff are expected to participate in patient care then access to relevant information and the ability to document their activities and patient interactions should be provided. The vital support role that security staff perform needs to be valued and respected. Abstract : Security staff are routinely called upon in EDs to assist in responding to behavioural problems. No prior research has been conducted exploring the views and experiences of security staff on this role in ED. This multi‐site qualitative study found that security staff are concerned about legal and safety issues and a lack of communication and respect from ED clinicians.